2020
DOI: 10.1002/jmd2.12104
|View full text |Cite
|
Sign up to set email alerts
|

ATP6AP1‐CDG: Follow‐up and female phenotype

Abstract: In 2016, 11 male patients were reported with immunodeficiency and hepatic, gastric and (in some) neurological disease due to X-linked ATP6AP1 deficiency (ATP6AP1-CDG). In 2018, three other patients were reported with additional features: connective tissue abnormalities, sensorineural hearing loss, hyperopia, glomerular and tubular dysfunction, exocrine pancreatic insufficiency and altered amino acid and lipid metabolism. We here present a followup of three reported siblings showing progression of deafness to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…In this cohort, 2822 samples were also investigated through collaborative initiatives of EUROGLYCAN (the years 2000–2003, 2822 analyses) and EUROGLYCANET (the years 2005–2009, 6098 analyses). Some of the patients have been previously reported [ [21] , [22] , [23] , [24] , [25] ].…”
Section: Methodsmentioning
confidence: 99%
“…In this cohort, 2822 samples were also investigated through collaborative initiatives of EUROGLYCAN (the years 2000–2003, 2822 analyses) and EUROGLYCANET (the years 2005–2009, 6098 analyses). Some of the patients have been previously reported [ [21] , [22] , [23] , [24] , [25] ].…”
Section: Methodsmentioning
confidence: 99%
“…Improvement of visceral and cutaneous manifestations has been previously reported in other CDG types 23,35,36 . However, hair loss and SNHL are apparently progressive over time 34 . P8, who is 67 years old at the time of evaluation, has a history of SNHL with onset at age 65, which could be age‐related.…”
Section: Discussionmentioning
confidence: 82%
“…Heterozygous females are generally asymptomatic and lack the main characteristic manifestations of the disease. The only potential manifestations from heterozygous females described in a single extended pedigree were proteinuria and SNHL (possibly age‐related) in 2/3 and 1/3 carrier mothers, respectively 1,34 . Their glycosylation studies were reported as normal, 34 although fractionated N‐glycan analysis was not performed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations